The Reaction of Polish Children’s Book Publishers to the Asylum Crisis (2015–2022): brak - Bednarek, Magdalena (Porównania, 2022)
Since 2016, Polish publishers have released 26 children’s books concerning refugees, victims of the crisis of migration policy, which started in Europe in 2015. Since then, the refugee question has become more direct and more important for Poland. Due to the crisis at the Belarussian border in 2021 and the war in Ukraine in 2022, refugees started to appear in the Polish territory, first in groups, later in masses. The aim of the article is to examine the correlation between dominant discourse on migration policy, geographical distance to crisis and cultural gap between Polish people and the refugees on the one hand, and the size of publishing houses and publishing policy of small, medium and large publishers on the other hand. The author describes the reactions of Polish children’s publishers in each phase of the crisis in Poland and the changing political attitudes towards refugees. A study on 51 publishers and 32 children’s books leads to the conclusion that the reaction to the refugee crisis depends on the size of a publishing house. Small and medium publishers are eager to engage in conflict with the dominant policy, whereas large publishers support refugees’ cause only if this cause is accepted by the dominant discourse.